Evaluasi Kinerja Modul Praktikum Pengkonversi Sinyal Analog ke Sinyal Digital Resolusi 8 Bit - Panangian Mahadi Sihombing; Ridho Akbar Pratama; Indah Vusvita Sari; Dona Tiara Lubis; Susilawati; Sari Novalianda (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2022)
The level of accuracy of an integrated circuit (IC) in converting signals is very necessary to achieve good system performance. One of IC device that is often used as analog to digital converter (ADC) is the IC ADC0804. This study aims to evaluate the work of a practicum module for converting analog signals to digital signals, namely the ETEK ACS-3000-07 Module. The module uses the IC ADC0804 to convert analog signals to digital signals. Two methods were used to test the performance of the module, namely the simulation method and the calculation method. Furthermore, the mean error and standard deviation methods are used to analyze the data that has been obtained. Based on the results of the analysis, it is known that the ETEK ACS-3000-07 Module still has sufficient performance in converting analog signals into digital signals because it has a mean error 0.36 and a standard deviation 0.48.